SAT-314 Pituitary and Neuroendocrine Tumors Exhibit Distinct Transcriptomes on Single Cell RNA Sequencing - Zhang, Dongyun (J Endocr Soc, 2020)
Neuroendocrine tumors (NETs) comprise a group of complex heterogeneous and increasingly prevalent neoplasms. They arise from diverse body regions, share derivation from primitive neuronal stem cells, secrete various bioactive peptides and exhibit a wide spectrum of tumor behavior from relatively indolent to rapidly progressive. Pituitary tumors represent 20% of intracranial tumors and share some features of NET histo-pathologic morphology, their excess hormone production and some have proposed re-naming pituitary tumors as PitNETs. However there has been no precise cell type composition comparison at the whole genome level in these two types of tumors. To explore intratumoral heterogeneity at a single cell resolution in pituitary and pancreatic NETs, we employed single cell RNA sequencing (scRNA-seq) to analyze in parallel cell populations from surgically resected pituitary tumors (n=4) and pancreatic NETs (pNET, n=2) using a 10x Genomics platform (v3). Using Cell Ranger pipeline for alignment and mapping, we obtained an average of 8,306±2,519 cells/sample with 1,516±822 genes/cell (mean reads/cell 67.9±30K). Seurat v3 was then used for read pre-filtering, normalization, and cluster identification. We identified 5 genes commonly expressed in both pNET and pituitary tumor populations, namely CALY (clathrin light chain binding GO:0032051), SPINT (peptidase inhibitor activity GO:0030414), CHGB (hormone activity GO:0005179), SCG5 (GTP binding GO:0005525) and SEZ6L2. As proof of their oral epidermal embryonic origin, the commonly expressed genes in 4 pituitary tumor samples include pituitary tissue restricted transcription factors (POU1F1, BEX1/2 GO:0033613), GNAS (G-protein beta/gamma-subunit complex binding GO:0031683), NLRP1 (peptidase activator activity involved in apoptotic process GO:0016505), PTN (protein phosphatase regulator activity GO:0019888) and ATP6V1G1 (ATPase binding GO:0051117). In parallel, 71 genes were present at high levels in pNET and involved in molecular functions such as calcium ion binding (HSPA5; ENPP2; C2CD4B; CALR; HSP90B1 GO:0005509) and endopeptidase inhibitor activity (PCSK1N; WFDC2 GO:0004866). Although our exploratory findings are limited to 6 samples, the robust commonly expressed genes within each tumor type clearly separated pituitary and pancreatic neuroendocrine tumors into distinct entities. We did observe conservation of chromogranins and prohormone convertases in these two tumor types, but it only represented a very small portion of overlap in transcriptome in pNETs. In summary, our findings suggest that pituitary and neuroendocrine tumors have only limited common molecular features, and by and large they stand as separate biologic populations. Our observations may begin to provide insight into the differences in tumor progression that are encountered clinically between pituitary tumors and pancreatic NETs.